2011
DOI: 10.1016/j.bandl.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Literal, fictive and metaphorical motion sentences preserve the motion component of the verb: A TMS study

Abstract: Order of Authors: Cristina Cacciari, PhD; Nadia Bolognini, PhD; Irene Senna; Maria Concetta Pellicciari, PhD; Carlo Miniussi, PhD; Costanza Papagno Abstract: We used Transcranial Magnetic Stimulation (TMS) to assess whether reading literal, nonliteral (i.e., metaphorical, idiomatic) and fictive motion sentences modulates the activity of the motor system. Sentences were divided into three segments visually presented one at a time: the noun phrase, the verb and the final part of the sentence. Single pulse-TMS wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 42 publications
4
69
3
Order By: Relevance
“…For example, in a fMRI experiment Raposo et al (2009) reported that action verbs activate motor regions when they appear in concrete literal sentences (e.g., kick the ball), whereas the same verbs in idiomatic sentences do not activate motor regions (e.g., kick the bucket). In the same vein, Cacciari et al (2011) employing single-pulse TMS on the left leg-related motor cortex while participants read leg-related action verb embedded in sentences, reported modulations of cortico-spinal excitability only when the action verbs appeared in a literal or metaphorical context, but not when the same verbs appeared in idioms.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in a fMRI experiment Raposo et al (2009) reported that action verbs activate motor regions when they appear in concrete literal sentences (e.g., kick the ball), whereas the same verbs in idiomatic sentences do not activate motor regions (e.g., kick the bucket). In the same vein, Cacciari et al (2011) employing single-pulse TMS on the left leg-related motor cortex while participants read leg-related action verb embedded in sentences, reported modulations of cortico-spinal excitability only when the action verbs appeared in a literal or metaphorical context, but not when the same verbs appeared in idioms.…”
Section: Introductionmentioning
confidence: 94%
“…Another alternative is that the activation of the motor cortex associated with reading is a non-automatic, context-dependent process, involving lexical-semantic integration across the sentence. The latter proposal is based on neuroimaging (Moody and Gennari, 2010;Schuil et al, 2013;Raposo et al, 2009;Urrutia et al, 2012), and brain stimulation studies (Cacciari et al, 2011;Buccino et al, 2005;Tomasino et al, 2008;Papeo et al, 2009). For example, in a fMRI experiment Raposo et al (2009) reported that action verbs activate motor regions when they appear in concrete literal sentences (e.g., kick the ball), whereas the same verbs in idiomatic sentences do not activate motor regions (e.g., kick the bucket).…”
Section: Introductionmentioning
confidence: 99%
“…was the grammar of the sentence correct or not). Furthermore, when rTMS was conducted on the right dorsolateral prefrontal cortex, the opposite pattern was visible, and the participants needed more time to finish the syntactic task, but did not need more time Manenti et al [39] Twelve right-handed, native Italian speakers Dorsolateral prefrontal cortex A double dissociation between the type of task (semantic vs. syntactic) and the rTMS effects was found, supporting the idea that the underlying working memory resources in sentence comprehension were processed differently by the two hemispheres Cacciari et al [42] Nine healthy participants…”
Section: Sentence Comprehensionmentioning
confidence: 48%
“…Larger motor-evoked potentials were found when individuals read literal, fictive, and metaphorical motion sentences than when they read idiomatic motion or mental sentences. Cacciari et al [42] found neuroscientific evidence for the hypothesis that the activity of the motor areas was affected by the motor component of the verb when reading fictive and metaphorical motion sentences.…”
Section: Motor Areamentioning
confidence: 99%
See 1 more Smart Citation